Akupunktur sebagai Terapi De Quervain’s Tenosynovitis - Sri Wahdini; Christina Simadibrata (Fakultas Kedokteran Universitas Riau, 2019)
De Quervain’s tenosynovitis is a disease with pain and edema in the styloid process due to thickening of the sheaths that encase the tendons of abductor pollicis longus (APL) and extensor pollicis brevis (EPB). Management of De Quervain’s tenosynovitis include pharmacotherapy combined with conservative therapy and if it fails then surgical intervention is required. In case of De Quervain’s tenosynovitis, acupuncture for relieving pain and stiffness. Reported the case of a woman aged 52 year, complaints of pain and stiffness in the left thumb since two months before went to the Poliklinik Akupunktur dr. Cipto Mangunkusumo Nasional Hospital. On physical examination the left wrist area found tenderness and spasm in the area of APL and EPB, VAS 4, there was limitation in the first carpometacarpal joint functional and Finkelstein’s test was positive. Acupuncture therapy done at the point LI5, LU7, LU9 and Ashi. There was pain reduction and functional improvement of the carpometacarpal joints. Acupuncture gives good results for pain and stiffness in patients with de Quervain’s.